The green healer: an updated review on the phytochemical profile and therapeutic potential of Aloe vera - Abid, Aimen; Javed, Mavra; Zafar, Saira; Hamdani, Syeda Andleeb Zahra; Shah, Syed Hassan Bin Usman; Abid, Juweria; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
Aloe vera has historically been recognized as a versatile medicinal plant, attributable to its extensive array of therapeutic properties. Recent scientific research has shown a diverse variety of bioactive compounds in Aloe vera that contribute to its potential pharmacological capabilities. This review synthesizes contemporary data on the phytochemistry, health benefits, and potential clinical applications of Aloe vera. Anthraquinones, flavonoids, polysaccharides, and other bioactive substances found in Aloe vera exhibit significant anti-inflammatory, antioxidant, antibacterial, and immunomodulatory effects. Furthermore, its nutritional composition is exceptionally varied, since Aloe vera contains prominent vitamins, minerals, and amino acids, rendering it an outstanding supplement for sustaining overall health. Its applications have been validated in the therapy of metabolic disorders, gastrointestinal recovery, improvement of dermatological conditions, and wound healing. Aloe vera continues to garner interest in both conventional and contemporary healthcare systems due to its affordability, accessibility, and safety profile as an integrative approach.